Bonding and short-range order in liquid silicon-carbon alloys - Kelires, Pantelis C. (My University, 1991)
Simulations of liquid silicon-carbon mixtures show that, at low pressures, the tendency of carbon towards low coordination dominates the overall structural characteristics. As a result silicon coordination is lower than in pure l-Si, accompanied by an enhancement of tetrahedral order and covalent bonding which persist in the liquid. The distribution of atoms is random in contrast to amorphous Si-C alloys. Under high pressures (1 Mbar) carbon coordination remains lower than four. At this pressure pure l-C is less dense than diamond.
Keywords: Silicon alloys; Carbon; Mixtures